PELATIHAN OLAHRAGA TRADISIONAL TEROMPAH PANJANG PADA MASYARAKAT DESA RIDOGALIH - Maulana, Rama; Basri, Hasan; Azhari, Adli; Ridha Kusuma, Rizki (Universitas Islam 45 Bekasi, 2024)
Nowadays, traditional sports are starting to be forgotten due to cultural shifts in technological developments in society, especially among teenagers. Therefore, there is a need for socialisation and training for teenagers in Ridogalih village, especially the people of hamlet 2 Ridogalih village. It is hoped that this seminar and training can attract teenagers' attention to traditional sports through the Terompah Panjang game. In addition, it is hoped that understanding and awareness of the many benefits of traditional sports will increase, such as improving physical fitness, psychomotor, affective, and cognitive. The method of service implementation uses socialisation and training. The results of the service showed that the teenagers were very enthusiastic in participating in this training, other results of the service activities were also seen from the results of the traditional terompah game which had seen progress in terms of cohesiveness and balance. So that this training can improve group cooperation and affective and psychomotor development.